Exposure to air pollution during childhood and risk of developing schizophrenia: a national cohort study. Issue 2 (February 2020) - Antonsen, Sussie; Mok, Pearl L H; Webb, Roger T; Mortensen, Preben B; McGrath, John J; Agerbo, Esben; Brandt, Jørgen; Geels, Camilla; Christensen, Jesper H; Pedersen, Carsten B
Summary: Background: Ambient air pollution affects neurological function, but its association with schizophrenia risk is unclear. We investigated exposure to nitrogen oxides (NOX ) as a whole and nitrogen dioxide (NO2 ) specifically, as well as PM10, and PM2·5, during childhood and subsequent schizophrenia risk. Methods: People born in Denmark from 1980 to 1984 (N=230 844), who were residing in the country on their tenth birthday, and who had two Danish-born parents were followed-up from their tenth birthday until schizophrenia diagnosis or Dec 31, 2016. Mean daily exposure to each pollutant (NO2, NOX, PM10, and PM2·5 ) at all of an individual's residential addresses from birth to their tenth birthday was modelled. Incidence rate ratios, cumulative incidence, and population attributable risks were calculated using survival analysis techniques. Findings: We analysed data between Aug 1, 2018, and Nov 15, 2019. Of 230 844 individuals included, 2189 cohort members were diagnosed with schizophrenia during follow-up. Higher concentrations of residential NO2 and NOX exposure during childhood were associated with subsequent elevated schizophrenia risk. People exposed to daily mean concentrations of more than 26·5 μg/m 3 NO2 had a 1·62 (95% CI 1·41–1·87) times increased risk compared with people exposed to a mean daily concentration of less than 14·5 μg/m 3 . The absolute risks of developing schizophrenia by the age of 37 years when exposed to daily mean concentrations of more than 26·5 μg/m 3 NO2 between birth and 10 years were 1·45% (95% CI 1·30–1·62%) for men and 1·03% (0·90–1·17) for women, whereas when exposed to a mean daily concentration of less than 14·5 μg/m 3, the risk was 0·80% (95% CI 0·69–0·92%) for men and 0·67% (0·57–0·79) for women. Associations between exposure to PM2·5 or PM10 and schizophrenia risk were less consistent. Interpretation: If the association between air pollution and schizophrenia is causal, reducing ambient air pollution including NO2 and NOX could have a potentially considerable effect on lowering schizophrenia incidence at the population level. Further investigations are necessary to establish a causal relationship. Funding: Lundbeck Foundation, Stanley Medical Research Institute, European Research Council, NordForsk, Novo Nordisk Foundation, National Health and Medical Research Council, Danish National Research Foundation.